Adverse childhood experiences and neuroinflammatory biomarkers—The role of sex. (14th June 2019) - Kim, Seoyoun; Watt, Toni; Ceballos, Natalie; Sharma, Shobhit
Abstract: Despite the growing interest in adverse childhood experiences and biomarkers, less attention has been paid to multiple biomarkers as representing interrelated systems among college students. Guided by the neuroinflammatory pathway hypothesis, the current project takes the initial step in examining the link between three types of childhood adversity and biomarkers of neuroplasticity (brain‐derived neurotropic factor [BDNF]) and low‐grade inflammation (C‐reactive protein [CRP]) in an overarching model and whether this link may differ in men and women. Undergraduate students ( n  = 85) were recruited through multiple departments from a state university. The participants responded to the detailed online survey questionnaire on childhood adversity and provided one blood sample via venous blood draw. Given that CRP and BDNF represent two interrelated systems, structural equation models were considered the most suitable for the analyses. The findings partially support neural and inflammatory pathways, such that childhood adversity and particularly family dysfunction have a significant positive effect on BDNF ( b  = 30.41, p  < .01). The link between family dysfunction and CRP was stronger in female students ( b  = 0.57, p  < .05). Results suggest that interventions for college students with family dysfunctions may need to target different physiological and behavioral outcomes for male and female students.